Introduction to C programming a modular approach - Collopy, David M. (Prentice Hall, 1997)
The text takes a "learn by example" approach to presenting C programming. It introduces one or more "realistic" sample programs in each chapter that relate concepts by illustrating how the material may be applied to an actual programming situation. Each chapter demonstrates application of the program development process, from start to finish.